Pengujian kinerja keuangan: Sustainable development goals sebagai intervening di Bursa Efek Indonesia - Farida, Ajeng Luthfiyatul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to examine and analyze financial performance as proxied by ROA (Return on Assets) and ROE (Return on Equity) with the influence of Corporate Social Responsibility (CSR) variables, the board of directors, and Sustainable Development Goals (SDGs) as intervention variable. The sample selection method uses a purposive sampling method that uses several criteria with the object of research being companies listed on the Indonesia Stock Exchange and the National Center for Sustainability Reporting (NCSR) in 2018-2020. Where the results of the data obtained amounted to 52 data obtained from secondary data. Data analysis used path analysis with Normality Test, Hypothesis Testing which was processed with SPSS Version 22 for windows. The results showed that: (1) Corporate Social Responsibility (CSR) had a significant positive effect on the Sustainable Development Goals (SDGs); (2) The board of directors has no significant effect on the Sustainable Development Goals (SDGs); (3) Sustainable Development Goals (SDGs) have a significant positive effect on financial performance; (4) Corporate Social Responsibility (CSR) has a significant positive effect on financial performance; and (5) the board of directors has no significant effect on financial performance.